On Extreme Waves in Directional Seas with Presence of Oblique Current. (July 2021) - Wang, Jinghua; Ma, Qingwei; Yan, Shiqiang
Highlights: The phase-resolved fully nonlinear numerical simulations of directional seas with presence of opposing and oblique current on large spatiotemporal scale are carried out. This study reports some new findings about how the fully nonlinear wave-current interactions modify the extreme wave properties in directional seas subject to current from different incident angles. The study also discusses whether the NewWave model is sufficient for describing the average shape of extreme waves induced by fully nonlinear wave-current interactions in directional seas. Abstract: This paper will address two questions: i) How the fully nonlinear wave-current interactions modify the extreme wave statistics, spectrum characteristics and average shape of extreme waves in directional seas subject to current with different incident angles; ii) Whether the NewWave model is adequate to describe the average shape of nonlinear extreme waves in directional seas with presence of opposing and oblique current. This study employs fully nonlinear numerical simulations, and the results demonstrate that current can enhance the wave crest exceedance probability at distribution tail and kurtosis, broaden the spectra, and cause severe vertical and horizontal asymmetry of extreme wave profiles depending on the incident angle and initial wave steepness. The assessment on the NewWave models reveals that they fail to predict the reduction of the crest width with increasing current incident angle and significantly underestimate the asymmetry parameters for large steepness waves.